Repair of rabbit cartilage defect based on the fusion of rabbit bone marrow stromal cells and Nano-HA/PLLA composite material. (2nd January 2017) - Zhu, Weimin; Guo, Daiqi; Peng, Liangquan; Chen, Yun Fang; Cui, Jiaming; Xiong, Jianyi; Lu, Wei; Duan, Li; Chen, Kang; Zeng, Yanjun; Wang, Daping
Abstract: Objective To assess the effect of the fusion of rabbit bone marrow stromal cells (rBMSCs) and Nano-hydroxyapatite/poly (l -lactic acid) (Nano-HA/PLLA) in repairing the rabbit knee joint with full-thickness cartilage defect. Method The rBMSCs were isolated and cultured in vitro, and the third generation of rBMSCs was co-cultured with the Nano-HA/PLLA to construct the tissue-engineered cartilage (TEC). Eighteen New Zealand white rabbits were selected and randomly divided into three groups, namely, TEC group, Nano-HA/PLLA group, and control group. A cartilage defect model with the diameter of 4.5 mm and depth of 5 mm was constructed on the articular surface of medial malleolus of rabbit femur. General observation, histological observation, and Wakitani's histological scoring were conducted in the 12th and 24th week postoperatively. Results The results of TEC group indicated that new cartilage tissue was formed on the defect site and subchondral bone achieved physiological integration basically. Histological and immunohistochemical analyses indicated the generation of massive extracellular matrix. In contrast, limited regeneration and reconstruction of cartilage was achieved in the Nano-HA/PLLA group and control group, with a significant difference from the TEC group ( p  < 0.05). Moreover, the effect of cartilage repair was positively correlated with time. Conclusion The porous Nano-HA/PLLA combined with BMSCs promoted the repair of weight-bearing bone of adult rabbit's knee joint with cartilage defect.